Enhancing Lecturer Development for Effective Quality Assurance Integration in Higher Education - Nyuma, Musakanyi Barbra; Claretah, Makuvire; Denius, Muzenda (Quality Assurance Practices for Transformative Higher Education in Southern Africa, 2025)
Introduction: Quality is at the heart of transformative education, and lecturers play a crucial role in providing quality education. This belief encourages to state that in as much as factors such as institutional support, curriculum design, and student engagement influence educational quality, the role of the lecturer remains critical. However, there is a need to emphasise in this chapter that the quality of human resources in any country is a necessity. To be specific, universities have a multifaceted nature of human resources, encompassing not only lecturers but also support staff, administrators, and policymakers. This refers to skilled and semi-skilled staff. Universities focus on constantly improving lecturers’ capacity for research, teaching, innovation and industrialisation skills, and knowledge that lecturers require. This is essential because they also have a direct impact on students' learning experiences. As a result, it is critical to assess the efficacy of lecturer development programmes in terms of higher education quality assurance management. Objective: The purpose of this chapter is to analyse the effectiveness of the lecturer development programme in enhancing teaching abilities and skills. Results: Universities can increase the quality of their teaching and research by implementing lecturer development programmes, which in turn boost their reputation. Thus, investment in lecturer development programmes can be considered a sustainable strategy to advance the quality of higher education and achieve the goal of developing quality human resources. It has also been found that a supportive institutional culture that prioritises quality assurance leads to better alignment between teaching practices and the desired learning outcomes. However, the challenges of lecture development programs involve the dynamics of technological change, globalisation, and demands for curriculum diversification. Along with these challenges, there are also ongoing innovations in the design and implementation of these programmes. Conclusion: Lecturer development was emphasised as a purposeful process that gives teachers the abilities and information they need to successfully negotiate the ever-changing terrain of teaching and learning, while integration was defined as the methodical incorporation of quality assurance concepts into all facets of instructional practice.